STUDY PROFIL MOOD ATLET PENCAK SILAT PADA KEJUARAAN MATARAM CUP TAHUN 2022 - Annisa Aprilia Muslim; Elya Wibawa Syarifoeddin; Indri Susilawati (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
The background of the problem in this study is about the mood of athletes competing in the 2022 Mataram Cup Championship. Mood is a temporary emotional state. Mood or mood can indeed change. Mood itself is an emotional state that arises only temporarily, divided into two, namely a good mood (good mood) and bad (bad mood). When someone is in a bad mood, the feelings they feel become more difficult to control emotions, so they can't concentrate when doing something. The purpose of this research is to determine the mood profile of athletes at the Mataram Cup Pencak Silat Championship in 2022. This research is aquantitative descriptive research, which is an analysis of data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public. The population in this study were all pencak silat athletes at the 2022 Mataram Cup Championship, totaling 115 people. The sampling technique in this study used a purposive sampling technique. with the criteria for male athletes in the senior category. so that 35 male athletes were obtained. Analysis of the data used is using descriptive percentage analysis method. Categorization uses the Mean and Standard Deviation and to determine the score criteria using the Norm Reference Assessment (PAN). Based on the results of data analysis obtained: From the results of data analysis and assessment of each criterion, the highest average percentage is at the